2 Bernard Bush, Laws of the Royal Colony of New Jersey 1703-1745, at 293 (1977) (passed May 5, 1722) - (:unkn) unknown (My University, 1722)
An Act to Prevent the Killing of Deer out of Season, and Against Carrying of Guns and Hunting by Persons not Qualified: That if any Person or Persons shall presume, at any Time after the Publication hereof, to carry any Gun, or Hunt on the Improved or Inclosed Lands in any Plantation, and on other than his own, unless he have Lisence or Permission from the owner of such Lands or Plantation, and shall be thereof Convicted, either upon the View of any Justice of the Peace within this Province, or by the Oath or Affirmation of any one or more Witnesses, before any Justice of the Peace, he shall, for every such Offence, forfeit the Sum of Fifteen Shillings, with Costs attending such Conviction.
Keywords: HUNTING REGULATION